Estudo do reconhecimento de micrornas expressos em Carcinomas Epidermóides de Cabeça e Pescoço (CECP) utilizando nanopartículas de prata - Oliveira, Jéssica Santana Assumpção de (2019)
Epidermoid Carcinoma of the Head and Neck is a type of malignant tumor that presents a heterogenous characteristic, since it affects different anatomical sites like, for example, the oral cavity, larynx and pharynx. The main problem associated with this neoplasia is the high number of deaths due to delays in diagnosis. The scarcity of public health resources, the high costs of performing tumor detection tests, the current methods of late diagnosis and other aspects contribute to the malignant cells spreading to adjacent tissues, decreasing the patients' expectations and quality of life. With the need to assist and improve current medical studies, the use of nanoparticles in medicine has become a very interesting aspect in creating products and new techniques to improve health. This is possible because these nanoparticles have a high potential in studies of monitoring, diagnosis and treatment of diseases in the early stages. This work aims to study silver nanoparticles (AgNPs) in the recognition of specific microRNAs for CEPC, with the objective of analyzing their activity as nanobiosensor, since their photochemical properties are unique and efficient for use as fluorescent probes. For this, the metastatic tumor markers miR-203 and miR-205 will be used. The methodology consisted in immobilizing oligonucleotides on the surface of AgNPs and then subjecting them to contact with the miR-203 and miR-205 targets. Results showed that only protocol 3 was efficient in the immobilization of oligo-miRs and that the interaction between the complex formed by the modified AgNPs and the microRNAs promoted a colloidal suspension staining change, indicating the specific annealing formed between the free end of the oligo-miR and their respective microRNAs. These results were confirmed by UV-Vis, FTIR and AFM techniques. The innovative character of the project is the fact that this specific interaction can contribute to different diagnostic methods due to the high sensitivity of the material to recognize small concentrations of the studied targets, which can act as a potent alternative in the early detection of CECP, thus improving the existing diagnostic techniques.